Molecular Motions and Interactions in Aqueous Solutions of Thymosin‐β4, Stabilin CTD and Their 1 : 1 Complex, Studied by 1H‐NMR Spectroscopy. Issue 13 (8th June 2020) - Bokor, M.; Tantos, Á.; Mészáros, A.; Jenei, B.; Haminda, R.; Tompa, P.; Tompa, K.
Abstract: Wide‐line 1 H NMR measurements were extended and all results were interpreted in a thermodynamics‐based new approach on aqueous solutions of thymosin‐β4 (Tβ4 ), stabilin cytoplasmic domain (CTD), and their 1 : 1 complex. Energy distributions of potential barriers controlling the motion of protein‐bound water molecules were determined. Heterogeneous and homogeneous regions were found in the protein‐water interface. The measure of heterogeneity of this interface gives quantitative value for the portion of disordered parts in the protein. Ordered structural elements were found extending up to ∼20 % of the individual whole proteins. About 40 % of the binding sites of free Tβ4 get involved in bonds holding the complex together. The complex has the most heterogeneous solvent accessible surface (SAS) in terms of protein‐water interactions. The complex is more disordered than Tβ4 or stabilin CTD. The greater SAS area of the complex is interpreted as a clear sign of its open structure. Abstract : Proteins wide shut : Thymosin‐β4 forms a complex with stabilin CTD, reflected by properties of mobile hydration water. The complex is more disordered than its constituting proteins, with Stabilin CTD being the most compact. Interaction sites belonging to hydrophilic parts of solvent accessible surface are involved in interactions holding the complex together. Hydration water, mobile at low potential barriers, is attributed to ordered protein structural patterns ranging from 10 to 20 %.